Rathaus – Bahnhof – Museum. Auswirkungen ausgewählter kommunaler und privater Einrichtungen auf das soziale Leben der Bevölkerung in Czernowitz zur Zeit der Habsburgermonarchie - Michaela Seewald (Historia.scribere)
The 19th century is - as regards urban planning - characterized by the development of infrastructure, such as schools or hospitals. These changes can also be observed in the eastern parts of the monarchy. The regional focus of this thesis lies on Czernowitz, the capital city of the Bukovina since 1849. Three institutions - the town hall, the railway station and the museum - serve as an example to show how the construction of these buildings had an impact on the social life of the residents of Czernowitz. The article shows that identity is the central connective element.